Your life plan : how to set yourself on the right path and take charge of your life - Sosna, Erica (Capstone, A Wiley Brand, 2014)
Meet the challenges of life and master your future Do you ever feel like you're just floating through life with a lack of direction? Or get that nagging feeling that things could be better? Then it's time you thought about your life plan. Our lives can be thought of as stories - as narratives and adventures - and nearly all classic stories share certain universal characteristics. Our lives should be seen as a hero's journey, a quest filled with challenges, turbulence and adventure. By appreciating this pattern, and understanding where you are on your own personal journey, you'll get the perspective needed to write your own life story and set yourself on the right path. Be the hero of your own life In Your Life Plan, Erica Sosna shows you how to choose and live a life that is truly meaningful, exciting and adventurous. Having a life project - a dream or goal that feels like a real challenge, can give you focus, energy and purpose. This book offers practical solutions and guidance for dealing with difficult personal challenges and becoming the victorious hero who achieves happiness and fulfilment. Go. Stand for something. Take up the charge and move into a purposeful and positive future.